Development of numerical algorithm for power system computation as project-based learning in numerical methods course - Syafii Syafii; Baik Budi (JPP (Jurnal Pendidikan dan Pembelajaran), 2025)
This article presents the application of a Project-Based Learning (PjBL) approach in the Numerical Methods course, focusing on developing a numerical algorithm for power system computation. The study addresses the challenges of efficiently calculating the bus admittance matrix (Ybus), bus numbering sequences, and handling double-line connections, all crucial for accurate power flow analysis. The objective is to create an efficient algorithm that can be applied to a 7-bus power system, enhancing students' practical skills in numerical methods. The results demonstrate that the algorithm successfully computes the Ybus matrix, resolves bus numbering issues, and handles double-line connections. This approach not only improves computational efficiency but also deepens students' theoretical knowledge and practical problem-solving abilities. The study highlights the effectiveness of PjBL in teaching numerical methods, offering valuable insights for its application in other engineering fields to enhance both learning and real-world problem-solving skills.